Deforestation and economic growth trends on oceanic islands highlight the need for meso-scale analysis and improved mid-range theory in conservation - Nitin Bhatia (Resilience Alliance, 2020)
Forests both support biodiversity and provide a wide range of benefits to people at multiple scales. Global and national remote sensing analyses of drivers of forest change generally focus on broad-scale influences on area (composition), ignoring arrangement (configuration). To explore meso-scale relationships, we compared forest composition and configuration to six indicators of economic growth over 23 years (1992-2015) of satellite data for 23 island nations. Based on global analyses, we expected to find clear relationships between economic growth and forest cover. Eleven islands lost 1 to 50% of forest cover, eight gained 1 to 28%, and four remained steady. Surprisingly, we found no clear relationship between economic growth trends and forest-cover change trajectories. These results differ from those of global land-cover change analyses and suggest that conservation-oriented policy and management approaches developed at both national and local scales are ignoring key meso-scale processes.